Development of platinum and platinum-tin deposited nitrogen doped novel copolymer-carbon nanotubes electrocatalyst for alcohol oxidation. (7th June 2017) - Selvaraj, V.; Thamil Magal, R.; Prasanna, D.
Abstract : The present work was emphasised to develop monometallic (Pt) and bimetallic (Pt-Sn) nanoparticles deposited poly[cyclotriphosphazene-co-(4, 4′-hexafluoroisopropylidene)dianiline] (PCFA) wrapped carbon nanotubes (CNTs) composite [Pt/PCFA-CNT and Pt-Sn/PCFA-CNT]. The synthesised Pt/PCFA-CNT and Pt-Sn/PCFA-CNT nanohybrids were characterised by X-ray diffraction, transmission electron microscopy and energy dispersive X-ray analysis. The above results confirm that the Pt and Pt-Sn nanoparticles are uniformly dispersed on bi-functional groups of PCFA in CNT with an average particle size of 2.0 nm. The obtained novel catalysts were utilised as anode material for electrocatalytic oxidation of methanol and ethylene glycol (EG). The electrocatalytic activities of the resultant nanohybrid catalysts were performed by cyclic voltammetry and chronoamperometric analysis in alkaline medium. The methanol and EG electrooxidations have low onset potential and higher oxidation peak current on Pt-Sn/PCFA-CNT when compared to that of Pt/PCFA-CNT. Further, the Pt/PCFA-CNT shows enhanced catalytic performance and low onset potential compared to that of the Pt/CNT and Pt/C catalyst, which might be due the synergistic effect of novel supporting material with the platinum metal nanoparticles that favours a direct pathway mechanism without the formation of CO poisoning.